Identificación de especies del género Colletotrichum asociadas a la antracnosis en papaya (Carica papaya L.) en Costa Rica1 - Molina-Chaves, Anthony (2017)
Identification of Colletotrichum species associated with anthracnose in papaya (Carica papaya L.) in Costa Rica. Anthracnose, caused by Colletotrichum spp., is one of the most important postharvest diseases in papaya. In this study, papaya fruits, Pococí hybrid, collected from orchards located in Guácimo, Limón province, showed 7 distinct anthracnose symptoms after a storage period. Colletotrichum isolates were obtained from each symptom on PDA (potato-desxtrosa-agar) medium. Isolates were classified in 3 groups based on symptoms similarities and colony morphology. Sequence analysis of the internal transcribed spacer (ITS) region revealed that isolates belonged to three Colletotrichum species: C. gloeosporioides sensu lato, C. magnum and C. capsici (C. truncatum). Species identification was confirmed using taxonspecific primer for C. gloeosporioides sensu truncatum (sinónimo C. capsici) (Tapia-Tussell et al. 2008, Nascimento et al. 2010, Tarnowski y Ploetz 2010, Rampersad 2011, Vieira et al. 2013, Torres-Calzada et al. 2013).